Survey Tentang Karakteristik Keluarga Siswa Yang Terlibat Balap Liar Di Smp Negeri 5 Tanah Putih T.A. 2013 / 2014 - Siti Aminah, Nina Siti Aminah Nina; Saam, Zulfaan Saam Zulfaan; Yakub, Elni Yakub Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This research entitle " Survey About Characteristic Family Student In Concerned Race Wild In SMPN 5 White Land;Ground of T.A 2013 / 2014". Pursuant to done/conducted by perception is writer pass/through passed to enquette is student, in the reality child in concerned wild race because of unfavourable family characteristic and treatment of parent to child. Target of this research is: 1). To know family karkteristik education storey;level, economic storey;level, and type work of old orng) student in concerned race wildly 2) To know treatment of old fellow to child behaviour and child in concerned race wildly. Method which is used in this research is data collecting method, by using passed to enquette is student. Population in this research is student - student of SMPN 5 White Land;Ground in concerned race wild which amount to 32 people. Result of data processing the got is student family characteristic in concerned race is wild the than storey;level education of father flatten - flatten alumna of SMA (46,87) % while education of alumna mother of SMP downwards is ( Low ) 62,5 %. Whereas from storey;level economics of student old fellow categorized is with earnings among/between Rp. 1.720.000 to Rp. 5.000.000. And seen from type work of student father of SMPN 5 White Land;Ground in concerned race wild most is wiraswasta 65,5% while work of mother is housewife equal to 68,75 %. From result of survey which have been done/conducted by hence can know by treatment of student old fellow to its unfavourable child amount to 66,18 %. Keyword :Characteristic Family And Race Wildly